- - رؤیا مقصودى دریه (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2002)
Through the application of citation method, the researcher endeavore to analyze 1819 citations extracted from 4 journal of libraiy and information science between the years of 1999-2000. The main objectives pursued in this paper includes, determining the most frequently cited of Farsi and non-Farsi periodicals, the kind and the language of the citations, as well as the contribution of co-authors in writing articles, showing the type of the paper, whether translation or original, the rank of the authors, and finally analysing the findings.